2014
DOI: 10.14202/vetworld.2014.970-975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding sweet sorghum stover based complete ration on nutrient utilization in Nellore lambs

Abstract: Aim: The present study was carried out to evaluate the nutrient digestibility of sweet sorghum stover, an unconventional roughage source in ram lambs in comparison to conventional sorghum and maize stovers.Materials and Methods: 18 Nellore ram lambs aged about 3 months (average body weight 15.65±0.10 kg) were randomly allotted to three complete rations formulated with roughage to concentrate ratio of 60:40 using sorghum stover (D1), maize stover (D2) and sweet sorghum stover (D3) as roughage source for a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[ 77 ] reported that mustard straw could be incorporated in complete feed for sheep up to 60% level without much adverse effect on voluntary feed intake and nutrient utilization. Moreover, it has been reported that SSB could be incorporated at 50% [ 15 ] while as sweet sorghum stover could be incorporated at 60% [ 78 ] level replacing conventional roughages such as sorghum stover and MS in complete diets for sheep. Similarly, Nagalakshmi et al .…”
Section: Feeding Complete Feedmentioning
confidence: 99%
“…[ 77 ] reported that mustard straw could be incorporated in complete feed for sheep up to 60% level without much adverse effect on voluntary feed intake and nutrient utilization. Moreover, it has been reported that SSB could be incorporated at 50% [ 15 ] while as sweet sorghum stover could be incorporated at 60% [ 78 ] level replacing conventional roughages such as sorghum stover and MS in complete diets for sheep. Similarly, Nagalakshmi et al .…”
Section: Feeding Complete Feedmentioning
confidence: 99%